THE ROLE OF TIKTOK IN ENHANCING ENGLISH LANGUAGE SKILLS: A SYSTEMATIC REVIEW - Maryam Jameelah; Muhoiriah; Naf’an Tarihoran (International Journal of Teaching and Learning, 2025)
The use of social media today has changed the nature of English language learning. One such social media platform is TikTok. This study aims to investigate the role of TikTok in enhancing English language skills using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. 22 studies published from 2020 to 2025 derived from ScienceDirect (1), ResearchGate (7), and Mendeley (14) are inspected to find out how TikTok influences undergraduate students’ speaking, listening, vocabulary acquisition, and pronunciation. The results indicate that TikTok is an effective tool that enhances English language learning and the students’ language skills through its interactive features like duet challenges and short videos. Additionally, TikTok increases student engagement by blending entertainment with education. However, challenges such as distractions, informal language exposure, and the need for guidance highlight the necessity of supervision by teachers. In conclusion, TikTok serves as an engaging and effective tool for enhancing English language skills particularly in speaking, listening, and vocabulary acquisition among undergraduate students.